Analysis of the Gap Between Taxable Profit and Accounting Profit and Its Impact on Tax Justice and Financial Stability: An Applied Study at the General Tax Authority of Iraq for the Period 2018-2025 - Hayder Koshan (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
The research aims Search to analysis gap between Profit Accountant And profit tax and statement Its effect in investigation Justice tax Stability Financial, That's from during study Applied in Authority public For taxes Iraqi during The period (2018–2025). It stems from importance Search from being Profit Accountant It represents a result Activity Economic According to For standards Accounting in when It is to set Profit tax According to For legislation and the laws Taxation, The matter that leads to appearance Differences or gaps between them a result difference Foundations Measurement and recognition In revenue And expenses, Please on Difference in Ways Calculation Consumption and allocations and some processors Accounting The other. It was adopted. Search on Curriculum Descriptive analytical in an offer Concepts Theory Related With profit Accountant And profit tax and justice Taxation, addition to Use Curriculum Applied To analyze Data Available For the period Time Specific, from during measurement size gap between The profit Analysis Its trends and its effect in The outcome tax Stability Financial. As well. It was completed Use group from Methods Statistics To analyze relationship between gap tax And all from Justice tax and stability Revenue The public. Access. Search to presence gap Note between Profit Accountant And profit tax during period the study, Return in part big From it to difference Rules Accounting And taxation, Please on some practices Related By avoiding tax weakness Coordination between The two systems Accountant And the taxpayer. And it showed Results that breadth This is amazing gap may leads to impact in level Justice tax between Those responsible, as may Reflected negatively on stability Revenue tax For the state.